AFFIXES FORMING INFLECTIONAL AND DERIVATIONAL VERBS IN KULISUSU LANGUAGE - Muhammad Dermawansyah,; Muhammad Darwis,; Asriani Abbas, (International Journal of Social Science, 2022)
Kulisusu language is the main communication tool in religious, traditional, and cultural activities. Development and study of regional languages to improve the language quality is needed. This is one way to respond to linguistic problems from phonemes, morphemes, words, phrases, clauses, sentences to discourse. However, this study only focuses on morphemes in form of affixes. Therefore, the researcher is interested in describing affixes forming inflectional and derivational verbs in Kulisusu language. This is beneficial for being inventory materials to develop Kulisusu language. This is a field research using qualitative descriptive method. Data collection was by interviewing, listening, and recording technique. The results showed affixes in Kulisusu language can form inflectional and derivational verbs. Inflectional verbs have 19 affix forms consisting of 8 prefix forms like: po-, mo-, pe-, me-, te-, in-, peka-, andmeka-,2 infix forms like: -um-, and-in-7 suffix forms like: -po, -mo, -o, -ako, -aka, -sakoand –si, and 2 confix forms namely: pa-oandpe-mo. Derivative verbs are divided into two types, namely, denominal verbs and deadjectival verbs. Denominal verbs have 12 affix forms consisting of 5 prefix forms namely: po-, mo-, pe-, me-,andko-,2 infix forms like: -um-and-in-, 2 suffix forms like: -akoand-aka,and 3 confix forms such as: po-i, mo-iandi-o.Deadjectival verbs have 5 affix forms consisting of 3 prefix forms namely: pa-, pompa-andmompa-, 1 suffix form like: -kiand 1 confix form like: pa-o.